The Role of Consulting in the Modern Economy - Dilrabo Malikova; Feruzakhon Abduganieva (Global Scientific Publishing, 2023)
The paper presents the essence of consulting services, varieties of consulting, the need to provide consulting services. Moreover, the article analyzes the domestic market of consulting services and presents proposals on the need to develop innovative consulting in Uzbekistan.
Keywords: economy; consulting; innovative consulting services; enterprises